Connection, Antiblackness, and Positive Relationships That (Re)Humanize Black Boys' Experience of School. Issue 1 (January 2022) - Warren, Chezare A.; Andrews, Dorinda J. Carter; Flennaugh, Terry K.
Background/Context: Black people continue to be popularly imagined as lacking humanity and, as such, are often the disproportionate subjects of unceasing race-gender terror and state violence. A vast body of scholarship has documented the failure of schools to adequately serve Black youth in general, and Black boys and men in particular. There is compelling evidence, however, that consistently humanizing interactions with adults in school lead to positive relationships that in turn may protect against Black boys' experience of school as fundamentally dehumanizing. Purpose/Objective/Research Question/Focus of Study: This study examined the significance of positive relationships between Black boys and adults in school as they move(d) across the P–16 education pipeline. The study is guided by the following primary research question: How do young Black men and boys describe and understand their interpersonal relationships with adults in P–16 schools? Research Design: A descriptive phenomenological approach was used to understand how 28 Black boys and young men discuss and describe the characteristics of relationships with adults in their school or university. Seven video- and audio-recorded focus groups were conducted. Data analysis occurred in three phases. Video clips from focus groups were analyzed in the first phase of data analysis. During the second phase of our data analysis, researchers employed critical race theory as a key analytic perspective to interpret the data for what they revealed about the ways anti-Black racism and white supremacy structured schooling experiences. The third phase of analysis centered on coding the entire data set, regardless of grade band, for three specific types of interactions: disciplinary/behavioral, social/relational, and academic. Findings/Results: Key findings from the study center on (a) these participants' keen awareness of the ways their words/behavior/actions are generally misread and misunderstood in U.S. society and (b) the significance of educators' race-gender perceptions of them in building positive relationships that establish and sustain authentic human connections. Conclusions/Recommendations: Human connection emerges over time and differentiates what our participants ultimately perceived as "good"/positive relationships from "bad"/negative relationships with educators. Recognition of the residual consequences of U.S. chattel slavery for the ways we see, know, and understand Black people and Black children is essential to cultivating positive relationships with Black boys. Although "bad" relationships are characterized by interactions reflecting racial misandry that Black boys come to expect as a normal, ordinary feature of their schooling experience, positive relationships are evidenced through consistently humanizing interpersonal interactions with adults that actively counter harmful racial scripts.